Marcel Proust : la Berma, figure de l’artiste, figure maternelle - NATUREL, Mireille (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
Marcel Proust : The Berma, Actress’ Figure, Motherhood’s Character. La Berma is an actress in Proust’s novel À la recherche du temps perdu. Her main model is Sarah Bernhardt and she has the same beautiful voice, a golden voice. Both of them are famous for their role of Phèdre in Racine’s drama. Theatre represents firstly a family matter and a social challenge. The child discovers theatre outside theatre where he is not allowed to go, that is on posters from the Morris column. And the first approach is semiotic. Theatre is included in narration, through two performances that the hero attends. With them, we have an image of theatre in the 19th century, from a sociological and artistic point of view. In the first one, theatre is considered as a low art and actresses are immoral women. Theatre is a cruel world which leads from glory to death, brings rivalry between actresses. In the latter, theatre is above all a text; Proust is interested in gesture and costume. He is focused on the quality of interpretation in comparison with the role. He shows that interpretation is a real art, which can be compared to painting and music.